1992
DOI: 10.1038/bjc.1992.249
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cis-diamminedichloroplatinum(II) resistance: a review

Abstract: Summary In this review an inventory is made of agents used to circumvent cis-diamminedichloroplatinum(II) (CDDP) resistance in vitro and in vivo. Agents that affect CDDP accumulation and membrane related systems, cytoplasmic defense mechanisms, as well as DNA accessibility and repair are reviewed.In resistant cell lines that have decreased accumulation, this can be restored by hyperthermic treatment. With or without effects on accumulation compounds that affect cell signal transduction often increase CDDP cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(73 citation statements)
references
References 76 publications
1
70
0
2
Order By: Relevance
“…One is the development of tumour resistance to the drug during therapy, leading to treatment failure. [4][5][6][7] The other is the drug's nephrotoxicity, which limits the dose that can be administered. 8 It is clear that much remains to be understood about the biophysical interactions of cisplatin with the cell membrane and with membrane-bound proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One is the development of tumour resistance to the drug during therapy, leading to treatment failure. [4][5][6][7] The other is the drug's nephrotoxicity, which limits the dose that can be administered. 8 It is clear that much remains to be understood about the biophysical interactions of cisplatin with the cell membrane and with membrane-bound proteins.…”
mentioning
confidence: 99%
“…However, from experiments with cell lines to which cisplatin was administered at concentrations above the normal pharmacological level, a number of factors have been identified as contributing to resistance. [4][5][6][7] At this stage, important mechanisms responsible for the development of cisplatin resistance appear likely to be: (1) decreased cytoplasmic accumulation of cisplatin, (2) increased levels of glutathione or glutathione-S-transferase activity, (3) increased levels of cytoplasmic metallothioneins, and (4) enhanced DNA repair. Here we will concentrate on the first of these possible mechanisms, i.e., decreased cytoplasmic accumulation of the drug.…”
mentioning
confidence: 99%
“…However, the presence of intrinsic or acquired resistance to cisplatin in cancer cells remains a major obstacle to successful cancer chemotherapy. Resistance to cisplatin in cultured cancer cells has been studied extensively and found to be multifactorial with drug accumulation defects (Eastman et al, 1986;Richon et al, 1987;Shen et al, 2000), increased detoxification mediated by glutathione or metallothionein (Moscow and Cowan, 1988;Kasahra et al, 1991;Shellard et al, 1991;Timmer-Bosscha et al, 1992), alterations of cell cycle regulators and signal transduction pathways (Basu et al, 1996;Kondo et al, 1996;Liu et al, 1996;Ruan et al, 1998), and increased repair of DNA damage (Barnes et al, 1993;Chu, 1994;Lai et al, 1995;Johnson et al, 1996;Fink et al, 1998). However, the exact mechanisms of cisplatin resistance require further elucidation.…”
mentioning
confidence: 99%
“…1) Some agents reversing cisplatin resistance have been developed. 8) We have previously reported that amphotericin B reversed cisplatin resistance.…”
mentioning
confidence: 99%